Pengaruh Fermentasi Actinobacillus sp. pada Kotoran Sapi sebagai Pupuk Terhadap Pertumbuhan Nannochloropsis sp. [Fermentation Of Actinobacillus sp. On Cow Dunk As Fertilizer On The Growth Of Nannochloropsis sp. ] - Rahayu Kusdarwati; Kismiyati Kismiyati; Linda Megawati Yanuaris (Faculty of Fisheries and Marine Universitas Airlangga, 2012)
Abstract Phytoplankton is a live feed that is needed by aquatic organisms and aquaculture, one of Nannochloropsis sp. Cow dunk has potential as an organic fertilizer in the culture of Nannochloropsis sp. Nitrogen and Phospore content of cow dunk to meet the growing needs of Nannochloropsis sp., so the cow dunk used as fertilizer can be environmentally friendly alternatives. Cow dunk is used as an alternative fertilizer fermented by the bacteria Actinobacillus sp. so that the content of N and P can be increased. N and P levels can be used Nannochloropsis sp. to grow and affect the population of Nannochloropsis sp. The purpose of this study was to determine the effect and optimal concentration of bacteria Actinobacillus sp. for the fermentation process cow manure as fertilizer in increasing the population of Nannochloropsis sp. The research design used was Completely Randomized Design (CRD). The optimum concentration of cow dung used was 10% with a five-day fermentation time. Culture over the last five days. Treatment of primary studies used were a control treatment D (Walne fertilizer), two control treatments E (fertilizers without fermentation), treatment A (under optimum bacterial concentration (7.5%)), Treatment B (optimum bacterial concentration (10% )), Treatment C (above the optimum concentration of bacteria (12.5%)). The results showed that the addition of fermented cow manure was cultured in sea water media can increase the population of Nannochloropsis sp. The best fermentation to produce the highest population is treatment B (optimum bacterial concentration (10%)) produces the highest population of Nannochloropsis sp. 2.175x106 cell/mL on the first day. Water quality parameters during the study is within the tolerance for the growth of Nannochloropsis sp., pH 7-8, room temperature between 30-31oC, ranging between 35-49 ppt salinity and water temperature ranges between 26-31oC.